The influence of Different Types of Career Exploration on Achievement Career Identity Among Z Generation - Abdullah Sinring; Nur Fadhilah Umar (Universitas Negeri Makassar, 2023)
This study aims to determine the effect of career exploration on the achievement of career identity, as well as various aspects of career exploration consisting of aspects of parental influence, economic status, personal choices, personal preferences, teacher influence, peer influence, the media, and which religious orientation most influential on identity career achievement. Using a correlational research design to determine how much influence the independent and dependent variables have. The data collection technique used a career development questionnaire. It developed from theory of the career development questionnaire, which EFA and CFA had tested to determine model fit, and both Career identity development inventories (CIDI). The sample in this study was students in South Sulawesi. The data analysis technique used was Pearson correlation and multiple regression analysis. Based on the findings, it was found that: 1. Career exploration on the career identity of generation Z students has a positive influence, 2. Several aspects of career exploration consist of personal choices, preferences, peer influence, and the media positively influencing career identity, 3. Aspects of career exploration that do not affect achievement career identity are parental influence, economic status, teacher influence, and religious orientation